Performance Evaluation of a Triple Concentric Tube Heat Exchanger Using Deionized Water and Oil-40 - Huda Majid Hasen (مجلة بغداد للعلوم)
This study examines experimentally the performance of a horizontal triple concentric tube heat exchanger TCTHE made of copper metal using water as cooling fluid and oil-40 as hot fluid. Hot fluid enters the inner annular tube of the TCTHE in a direction at a temperature of 50, 60 and 70 oC and a flow rate of 20 l/hr. On the other hand, the cooling fluid enters the inner tube and the outer annular tube in the reverse direction (counter current flow) at a temperature of 25 oC and flow rates of 10, 15, 20, 25, 30 and 35 l/hr. The TCTHE is composed of three copper tubes with outer diameters of 34.925 mm, 22.25 mm, and 9.525 mm, and thicknesses of 1.27 mm, 1.143 mm, and 0.762 mm, respectively. TCTHE tube's length was 670 mm. Nusselt number, overall heat transfer coefficient, convective heat transfer coefficient (CHTC), friction factor and pressure drop were measured from the obtained experimental results and plotted in graphs against Reynold number and volumetric flow rate of water. These parameters appeared good results in the cooling process. Nusselt numbers increased linearly with DIW flow rate for both C1 and C2 reaching maximum values of 38.25 and 14.64 respectively. CHTC increased linearly with the DIW flow rate for both C1 and C2 reaching maximum values of 2934.3 and 871.7 respectively. Overall heat transfer coefficient of DIW reached maximum values of 296.36 and 251.4 at 35 l/hr for C1 and C2, respectively. Friction factor DIW in C1 and C2 decreased with the volumetric flow rate increases, reaching minimum values of 0.04 and 0.25 respectively. Pressure drop of DIW increased linearly with flow rate reaching maximum values of 81.4 and 4.31 for C1 and C2 respectively. This in turn leads to reduced TCTHE length and size leading to a decrease in the construction cost of the heat exchanger.